2017
DOI: 10.1136/bmjopen-2016-013616
|View full text |Cite
|
Sign up to set email alerts
|

Financial modelling of femtosecond laser-assisted cataract surgery within the National Health Service using a ‘hub and spoke’ model for the delivery of high-volume cataract surgery

Abstract: AimsTo develop financial models which offset additional costs associated with femtosecond laser (FL)-assisted cataract surgery (FLACS) against improvements in productivity and to determine important factors relating to its implementation into the National Health Service (NHS).MethodsFL platforms are expensive, in initial purchase and running costs. The additional costs associated with FL technology might be offset by an increase in surgical efficiency. Using a ‘hub and spoke’ model to provide high-volume catar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…Similar conclusions have been drawn by Roberts et al, who explored how FLACS could be implemented in the NHS so that it is cost-neutral, using the model of 2 theaters functioning in parallel and staff working across them both. 35 They came to the conclusion that theaters would need to increase their list size by 100% or the cost of the patient interface would need to decrease by 70% for FLACS to approach cost-saving. Based on the results of a decision model, Abell et al came to similar conclusion that FLACS would need to significantly improve patient outcomes to be cost-effective in an Australian setting.…”
Section: Discussionmentioning
confidence: 99%
“…Similar conclusions have been drawn by Roberts et al, who explored how FLACS could be implemented in the NHS so that it is cost-neutral, using the model of 2 theaters functioning in parallel and staff working across them both. 35 They came to the conclusion that theaters would need to increase their list size by 100% or the cost of the patient interface would need to decrease by 70% for FLACS to approach cost-saving. Based on the results of a decision model, Abell et al came to similar conclusion that FLACS would need to significantly improve patient outcomes to be cost-effective in an Australian setting.…”
Section: Discussionmentioning
confidence: 99%
“…The results from this were used as inputs for a hypothetical economic model, reported in a previous publication, to determine an estimation of the costs of cataract surgery 11. This financial model has been described in greater detail in the previous publication but was based on averaged costs/values from five different NHS foundation trusts and four FL manufacturers.…”
Section: Methodsmentioning
confidence: 99%
“…Potentially, if the number of cases per theatre session can be increased sufficiently, then the additional costs associated with FL technology might be offset. In a previous publication, we have previously explored this possibility using a hypothetical model based on real-world financial data 11. We reported that in order to break even, there would need to be, for example, a 43% increase in the number of operations performed per theatre list accompanied by a need to discount the cost of the PIs by at least 52% by the manufacturers 2…”
Section: Introductionmentioning
confidence: 99%
“…Based strongly on this assumption, the additional cost of FL was estimated to be AUS$1065 per eye, AUS$750 of which were the direct costs from the FL and AUS$315 from reduced output. 116 Realising that any new technology in cataract surgery faces an uphill struggle in widespread adoption if it reduces efficiency, Roberts et al 120,121 have investigated the economic implications of using a FL as part of a hub-andspoke model to deliver high volume cataract surgery. This model features a laser in a dedicated anteroom and supplying patients to multiple theatres running in parallel.…”
Section: Economic Implications Of Flacsmentioning
confidence: 99%